Fatal imaginations: death squads in Davao City and Medellín compared - Oude Breuil, Brenda Carina (2009)
This article examines the role social imaginations play in legitimizing extrajudicial killings by death squads in the era of globalization. The role of popular imagining has expanded into a widespread social practice as people increasingly draw on images from all over the world via modern communication technologies. Drawing on Mary Douglas' concept 'matter out of place' and Nancy Scheper-Hughes' 'symbolic apartheid' we argue that to a certain extent, dehumanizing imaginations about socially excluded groups legitimize death squad killings. The article compares two case studies on death squads in the cities of Medellín, Colombia and Davao City, Philippines. We conclude that social imaginations in the era of globalization may be a driving force behind death squads in these and other major cities in the world.